PETROLOGY AND GEOCHEMISTRY OF THE VOLCANIC ROCKS DREDGED FROM THE GEOPHYSICIST SEAMOUNT IN THE KURILE BASIN: EVIDENCE FOR THE EXISTENCE OF THINNED CONTINENTAL CRUST - Tararin I.A.; Lelikov E.P.; Werner R. (My University, 2003)
Dredged samples from the Geophysicist seamount volcano in the northeastern part of the Kurile Basin include volcanic and volcanoclastic rocks ranging from basalt to andesite. The rocks have geochemical features typical of high-K island-arc calc-alkaline volcanism. They are enriched in LILE and depleted in Zr, Ti, Nb, Ta and Y. The chondrite-normalized REE patterns are characterized by enrichment of LREE similar to those of island-arc lava from the submarine volcanoes of rear-arc zone of the Kurile Island Arc. The volcanic rocks have a wide range of 87Sr/86Sr ratios (0.70287-0.70652), varying 143Nd/144Nd and Pb isotopic ratios. Their trace-element compositions and Sr-Nd-Pb isotope signatures may be explained by a small addition of crustal continental component to mantle-derived magmas that suggest the existence of thinned continental basement under the eastern part of the Kurile Basin.
Keywords: Geophysicist seamount volcano; geochemistry; interaction of basic magma with thinned continental crust; Kurile Basin; Sea of Okhotsk